Preferensi Generasi Z untuk Berinvestasi pada Instrumen Surat Berharga Negara - Pribadi, Yanuar (BISNIS, 2024)
Government Securities are becoming an alternative for retail investors for investing in Indonesia. It matched the goals of government financing to expand the domestic financial market. On the other side, Indonesia has had a demographic bonus from its population that is dominated by the young generation, especially Generation Z (born in 1997-2012). It could be an opportunity for the government to broaden the domestic bond financial market using Gen-Z as a catalyst or potential investor. The government needs to collect information regarding their investing preferences, especially in government securities. This research uses the Analytical Hierarchy Process (AHP) approach to determine investment alternatives priority for Gen-Z. The research results show that the ORI has become the favorite for Gen-Z to invest in government securities. The government has to keep on intensifying financial literacy, investing awareness, and information through social media about government securities instruments to achieve the goals of domestic financial market growth.